2017
DOI: 10.1002/pon.4553
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic effects of coping strategies, time perspectives, and personality on the quality of life of cancer patients and their caregivers

Abstract: The examination of the relationships between individuals' QoL and their internal psychobehavioral processes and personality traits will have several applications in the routine clinical management. Individual-level and dyad-level interventions should be proposed: cognitive-rehabilitation, emotional and cognitive self-regulation for time perspectives, and personality constructs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 38 publications
2
22
0
5
Order By: Relevance
“…Regarding the year of publication, 36 out of 62 articles were published in 2017 and 28 in 2018. Countries where the respective studies were conducted were the USA/Canada ( n = 23) [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31], Scandinavia ( n = 7) [32,33,34,35,36,37,38], UK ( n = 4) [39,40,41,42], Germany ( n = 4) [43,44,45,46], Southern Europe (Italy, Portugal, Spain; n = 8) [47,48,49,50,51,52,53,54], East Asia (Japan, China, Korea, Taiwan; n = 4) [55,56,57,58,59,60], Australia/New Zealand ( n = 4) [61,62,63,64], other ( n = 4) [65,66,67,68], and multinational ( n = 2) [69,70].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the year of publication, 36 out of 62 articles were published in 2017 and 28 in 2018. Countries where the respective studies were conducted were the USA/Canada ( n = 23) [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31], Scandinavia ( n = 7) [32,33,34,35,36,37,38], UK ( n = 4) [39,40,41,42], Germany ( n = 4) [43,44,45,46], Southern Europe (Italy, Portugal, Spain; n = 8) [47,48,49,50,51,52,53,54], East Asia (Japan, China, Korea, Taiwan; n = 4) [55,56,57,58,59,60], Australia/New Zealand ( n = 4) [61,62,63,64], other ( n = 4) [65,66,67,68], and multinational ( n = 2) [69,70].…”
Section: Resultsmentioning
confidence: 99%
“…Forty-seven studies reported on relatives of advanced cancer patient’s [9,10,11,13,15,16,17,18,19,20,21,22,23,24,26,27,28,29,30,31,32,34,36,37,38,39,42,43,44,46,47,48,49,50,51,52,53,55,56,57,58,59,60,61,65,66,67] and 15 studies included relatives of mixed patient samples [12,14,25,33,35,40,41,45,54,62,63,64,68,69,70]. The environment in which the patient received palliative or hospice care were home care in 18 studies [10,14,25,26,27,30,3...…”
Section: Resultsmentioning
confidence: 99%
“…While the coping strategies employed depend on the cognitive, behavioral and social resources that the patients and caregivers are able to mobilize, this result suggests that people who know each other very well and who are faced with the same difficult event tend to cope with it similarly. This phenomenon was already described in the context of ARHL [19], but has also been described in other contexts, such as cancer [15, 16] and mental illnesses [17].…”
Section: Discussionmentioning
confidence: 64%
“…In particular, the personal ability to cope, defined as the cognitive and behavioral efforts that the individuals implement to solve problems and reduce the stress that may result [11–13], has previously been shown as having a direct impact on the QoL of the individuals. More interesting, the nature of individuals’ coping strategies may have a direct impact on the QoL [14] of their natural caregivers as shown in various contexts, such as cancer [15, 16] or severe mental disease [17]. These different studies showed that positive thinking or problem solving seem to be preferentially associated with better QoL, and the use of strategies based on avoidance or social support appear to be a risk factor for lower QoL [1518].…”
Section: Introductionmentioning
confidence: 99%
“…the use of avoidance strategies), the more impaired are skin‐related QoL, psychological distress and self‐esteem. Consistently, studies assessing the influence of coping on general QoL in patients with physical diseases, for example, cancer, type 2 diabetes and systemic lupus erythematosus, outlined that the endorsement of maladaptive coping strategies (e.g. behavioural and mental disengagement) impact negatively on QoL and psychological well‐being.…”
Section: Discussionmentioning
confidence: 94%